(untitled) (Kinesiology, 2022)
This study investigated the etiology of neuromuscular fatigue induced by a 5-m shuttle run test (5MSRT) in soccer players. Nineteen adult male amateur soccer players (age: 20.0 ± 2.9 years) participated in the present study. Before and after the 5MSRT, they were instructed to complete a maximal voluntary isometric contraction (MVIC) of the knee extensors (KE) during and after which two electrical stimulations were applied at the femoral nerve. Voluntary activation level (VAL), surface electromyography recordings (sEMG), electrophysiological (Mmax) and potentiated resting twitch (Ptw) responses of the KE were compared between pre- and post-5MSRT. Rating of perception exertion (RPE) was also assessed before, during the test immediately following each sprint repetition and after the test. The distance covered during each sprint significantly decreased as the number of trials performed increased (p<.05). The RPE reported following each sprint significantly increased throughout the test. In addition, MVIC (-9%), sEMG (-23%), VAL (-15%), Ptw (-26%) and Mmax ( 22%) of the KE were lowered from pre-to-post 5MSRT (.001 < p < .01). The 5MSRT induced a decrease of repeated-sprint running performance and MVIC of the KE. These decrements were accompanied by lowered VAL, sEMG, Ptw and Mmax values of the KE reflecting the involvement of both the central and peripheral origins in the 5MSRT-induced fatigue. Given the important muscle stress induced by 5MSRT, this strenuous test must be applied with caution, after an inevitable familiarization phase, and not during the competition period to avoid the risk of serious injury. Key words: knee extensors, electrical stimulation, electromyography, repeated-sprint ability, perceived exertion